Medical Laboratory Sciences: Current Practices, Technological Innovations, and Future Directions in Clinical Diagnostics - AlShahrani, Bader Saad; Bajawi, Manal Yahya; Bajawi, Yasser Ali; Saqyan, Abdulelah Alhumaidi Bin; Alenazi, Mamdouh Muhareb (Journal of Posthumanism, 2025)
Medical laboratory sciences represent a cornerstone of modern healthcare, providing critical diagnostic information that guides clinical decision-making and patient care. This comprehensive review examines the current state of medical laboratory practices, emerging technological innovations, and future directions in clinical diagnostics. The paper explores key areas including automation and artificial intelligence integration, molecular diagnostics advancements, point-of-care testing developments, and quality assurance protocols. Through analysis of recent literature and technological developments, this review identifies significant trends including the increasing adoption of AI-powered diagnostic tools, the expansion of personalized medicine approaches, and the growing importance of laboratory information systems. The COVID-19 pandemic has accelerated innovation in diagnostic technologies, highlighting both opportunities and challenges in laboratory medicine. Future directions point toward greater integration of digital health technologies, enhanced predictive analytics, and improved patient-centered care delivery models. This review provides healthcare professionals, laboratory scientists, and policymakers with insights into the evolving landscape of medical laboratory sciences and their critical role in advancing healthcare outcomes.